Money Market Integration - Bartolini, Leonardo (IMF Working Papers; Working Paper, 2006)
We use transaction-level data and detailed modeling of the high-frequency behavior of federal funds and Eurodollar yield spreads to provide evidence of strong integration between the federal funds and Eurodollar markets, the two core components of the dollar money market. Our results contrast with previous evidence of segmentation of these two markets, showing them to be well integrated even at high intra-day frequency. We document several patterns in the behavior of federal funds and Eurodollar spreads, including liquidity effects from trading volume to yield spreads volatility. Our analysis supports the view that targeting federal funds rates alone is sufficient to stabilize rates in the, much larger, dollar money market as a whole.